Underwater Birth. Issue 5 (4th September 2013) - Simpson, Kathleen Rice
ABSTRACT: Objective: To determine potential risks and/or benefits of underwater birth for mother and infant. Data Sources: The PubMed, Cochrane Library, EMBASE, and CINAHL online databases were searched for relevant English language articles related to research about underwater birth published from 1966 to April 2013. Reference lists of articles retrieved were reviewed to identify additional potentially pertinent publications. Study Selection: Two randomized controlled trials comparing underwater birth to traditional birth ("on land") were identified and served as the primary focus of the analysis. One systematic review of water immersion during labor and birth, one systematic review of neonatal risks of underwater birth, and case reports of neonatal morbidity after underwater birth were also identified. Guidelines regarding underwater birth from professional organizations were reviewed. Data Extraction: Data from the two randomized controlled trials were extracted and organized under the following headings: author, year, setting, country, study design, sample size, participants, outcomes, findings and comments. Systematic reviews, case reports, and guidelines from professional organizations were summarized. Data Synthesis: Research findings and guidelines from professional associations were evaluated regarding potential risks and benefits of underwater birth to the mother and infant. Conclusions: Only two randomized controlled trials comparing underwater birth to birth on land have been published. Results suggest minimal benefit of underwater birth to the mother and no benefit to the infant. Both studies were underpowered to adequately evaluate risk of neonatal harm; however, a number of cases of neonatal morbidity have been reported. Based on these findings, underwater birth requires more rigorous study. In the United States, underwater birth is not supported by the American Academy of Pediatrics or the American College of Obstetricians and Gynecologists outside the context of a randomized controlled trial.